MARKETING STRATEGY AND COMPANY PERFORMANCE: THE MEDIATING ROLE OF CUSTOMER SATISFACTION - Ni Komang Mela Tri Utari (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study analyzes the role of customer satisfaction in mediating the influence of marketing strategies on company performance in an Indonesian communications company. The marketing strategy variables examined include brand image, pricing strategy, and product innovation. Previous research has examined the influence of marketing strategies on company performance, but the mediating role of customer satisfaction has received limited attention, particularly in the telecommunications service industry. This study uses a quantitative approach with an associative method. The research sample of 50 respondents who are IndiHome customers in Bali, was selected using purposive sampling techniques. Although the sample size is relatively small for regression analysis, it meets the minimum requirement for statistical testing and is therefore considered acceptable. The results show that brand image, pricing strategy, and product innovation have a significant effect on customer satisfaction. Furthermore, customer satisfaction has been proven to have a positive effect on the company's performance. The Sobel test confirms that customer satisfaction plays a significant role as a mediator in the relationship between marketing strategy and company performance. Thus, this study confirms that marketing strategies will have a greater impact on company performance if supported by a high level of customer satisfaction.